2018
DOI: 10.1007/s11420-018-9614-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction After Total Knee Replacement: A Systematic Review

Abstract: Background:The quality and state of satisfaction reporting after total knee replacement (TKR) is variable.Questions/Purposes:The purposes of this systematic review were (1) to examine the available literature on patient satisfaction after TKR, (2) to evaluate the quality of available evidence, and (3) to identify predictors of patient satisfaction after TKR.Methods:A systematic review of the MEDLINE database was performed. The initial search yielded 1219 studies. The inclusion criteria were English language, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
237
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(253 citation statements)
references
References 22 publications
5
237
0
11
Order By: Relevance
“…Complications of knee replacement surgery are similar to those of arthroscopy, including infection (seven per 1000) and pulmonary embolism (four per 1000) . Additionally, up to 18% of total knee replacements fail within 25 years, potentially requiring revision, and up to one in five patients who undergo total knee replacement are unsatisfied with the procedure . The risk of adverse events may be acceptable to many patients given the potential benefits from effective treatment, especially for those with more severe symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of knee replacement surgery are similar to those of arthroscopy, including infection (seven per 1000) and pulmonary embolism (four per 1000) . Additionally, up to 18% of total knee replacements fail within 25 years, potentially requiring revision, and up to one in five patients who undergo total knee replacement are unsatisfied with the procedure . The risk of adverse events may be acceptable to many patients given the potential benefits from effective treatment, especially for those with more severe symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on 95560 patients underwent total knee arthroplasty stated that 83% of the studies reported more than 80% satisfaction. (15) With increasing life expectancy, conduction of total knee and hip arthroplasty is rising too to improve the quality of life and movement. We also witnessed a low rate of post-operative complication for the two operations in our study, which was in agreement with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is a highly successful procedure in enhancing quality of life, restoring function and independence, as well as reducing pain for patients with joint diseases . To improve TKA further, there was a shift in focus towards earlier recovery, minimizing blood loss and reducing post‐operative pain, in the hope of achieving a higher overall satisfaction …”
Section: Introductionmentioning
confidence: 99%